Fenomenologia do Atendimento Psicológico On-Line no Contexto de COVID-19 - BRASIL, Anderson de Oliveira (2023)
Study on online psychological care in the context of COVID-19, using an online form (google forms) as a data collection instrument. For this, it aimed to reveal how psychology professionals, based on their experiences, describe online psychological care and the phenomena that emerge from it, in the context of COVID-19. This modality of psychological care has its origins in Brazil since the end of the 1990s, and as foreign literature shows, in a period prior to that, they date back to the 1980s, under the concept of E-therapy or telepsychology services. It is standardized by the Federal Council of Psychology (CFP) with resolution No. 11/2018/CFP. With the misfortune of the COVID-19 pandemic, the same Council launched Resolution nº 04/2020, on a provisional basis that does not revoke the previous one. This model proved to be the most important possibility for psychological contact during the pandemic, as face-to-face consultations were suspended and there was greater demand for online consultations. This investigation was developed through a qualitative non-experimental empirical research of Husserlian phenomenological orientation. The phenomenology and the phenomenological method proposed by Edmund Husserl made it possible to highlight 4 main themes through the intentional analysis of the professionals' experiences in relation to the world of life and the surrounding world of the participants. In addition, it also allowed the unveiling of exemplary individual essences, favoring the understanding of how subjectivity phenomena; intersubjectivity; empathy; psychotherapeutic bond and ethics were shown in the experiences of the participants. It is concluded that there are ambiguities inherent to the model; idiosyncrasies of each demand; psychotherapeutic bond similar to face-to-face; the body as the first mediator and the online environment as the second mediator of the relationship, or an auxiliary mediator of the psychotherapeutic contact.